EXPERIMENTAL STUDY ON THE PRESENCE OF OPEN CAVITY EFFECTS ON INTERNAL FLOW AND CONVECTIONHEAT TRANSFER CHARACTERISTICS (Journal of Engineering, 2010)
An experimental study is conducted to investigate the effect of open cavity on the pattern of fully developed internal flow and convection heat transfer. In this experimental work the velocity profile, temperature distribution, heat transfer coefficient and Nusselt number were determined at various Reynolds numbers (1.9*104≤ Re ≤ 2.7*104) for smooth surface as well as for flow over open cavity (with and without excitation). The results showed that the presence of the cavity led to change the downstream velocity profile and the dissimilarity of downstream skin friction coefficient between the upper and lower surfaces around (64 %) at distance to the length cavity (x/L= + 20.5). As a result the heat transfer coefficient and Nu increased downstream of the cavity especially at (x/L= + 20.5) around (30 %). The effect of cavity excitation with different  sound levels (100,107.5 and 115) dB and frequencies (25,50 and 100) Hz was small compared with the cavity itself.